2013
DOI: 10.1177/1756287213509849
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional collagenase in the treatment of Peyronie’s disease

Abstract: The objective of intralesional pharmacotherapy in the treatment of Peyronie's disease is to deliver large doses of pharmacologic agents that can have a local effect on wound remodeling, with minimal side effects. Guidelines for the treatment of peyronie's disease published in the Journal of Sexual Medicine and the European Association of Urology offer no grade A evidence of efficacy with multiple agents such as steroids, verapamil and interferon. Intralesional collagenase is the first drug to be approved by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Further, collagenase as a biologic has been recently approved by the FDA (XIAFLEX®, Auxilium Pharmaceuticals) to treat Dupuytren's contracture 31 and Peyronie's disease 32 . With proper characterization and future studies to examine the effect of collagenase in more detail, FDA approval to enhance fat grafts with collagenase-isolated SVF may be imminent.…”
Section: Discussionmentioning
confidence: 99%
“…Further, collagenase as a biologic has been recently approved by the FDA (XIAFLEX®, Auxilium Pharmaceuticals) to treat Dupuytren's contracture 31 and Peyronie's disease 32 . With proper characterization and future studies to examine the effect of collagenase in more detail, FDA approval to enhance fat grafts with collagenase-isolated SVF may be imminent.…”
Section: Discussionmentioning
confidence: 99%
“…It works by breaking down the extra collagen in the penis that causes this disease [115]. A multicenter, double-blind, phase 3 randomized and placebo-controlled trial supports the efficacy and safety of intralesional CCH in the treatment of the subjective and objective aspects of significant Peyronie's disease in patients with curvature between 30° and 90° [116,117]. Recent studies demonstrated that CCH treatment administered in multiple cycles led to significant benefit in both the psychological and physical aspects of Peyronie's disease.…”
Section: Collagenase As Debriding Agent In Wound Healingmentioning
confidence: 87%
“…These enzymes are not cysteine peptidases but serine peptidases, called brachyurins and are optimally active at neutral pH. Enzymes with collagenase activity have important therapeutic applications such as in wound healing (Agren et al 1992), treatment of Peyronie's disease (Honig 2014) and Dupuytren's contracture (Hurst et al 2009). Therefore, future studies by our group will assess if H. americanus cysteine cathepsin L2 has biochemical characteristics that are superior to the current therapeutic collagenases.…”
Section: Discussionmentioning
confidence: 99%